Wound infection following surgery in an accident and emergency theatre. Issue 1 (March 1984) - Spence, R A; Rutherford, W H
Abstract : Five hundred and six clean minor surgical procedures were carried out in an emergency theatre. One theatre was used for both clean and septic conditions; clean cases preceding the septic lesions. Sepsis rates were assessed prospectively and complete follow-up was obtained in 491 patients. Four hundred and fifty (91.6%) patients achieved primary healing. Thirty (6.1%) patients developed a mild serous discharge; three developed wound haematomas and eight (1.6%) patients had severely infected wounds with a purulent discharge. From the acceptably low incidence of severely infected wounds with a purulent discharge. From the acceptably low incidence of severely infected wounds we conclude that there is no need for separate clean and septic theatres in an emergency department provided the clean operations are comparatively short and simple procedures.